The Influence of Learning Media and Motivation on the Learning Outcomes of Short-Distance Running - barkah sekar kalih; Iwan Hernawan; Ika Novitaria Marani; Oman Unju Subandi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2023)
This study aims to determine the influence of learning media and learning motivation on the learning outcomes of short-distance running. This research was conducted at SMPN 15 Depok class VII. This research method uses experimental research with a treatment design by level 2x2. The sample in this study consisted of 60 people. Sample collection using simple random sampling technique. The data analysis technique is two-path variance analysis (ANAVA) and is continued with the Tukey test at a significant level ɑ = 0.05. To test the normality of the data, use the kolmogorv-smirnov test and the homogeneity test using the levene test. The results of this study show that (1) Overall visual learning media is better than the use of audio learning media based on the value of F (OA) = 21.11 with p-value = 0.000 < 0.05. (2) There is an influence of interaction between learning media and motivation on short-distance running learning outcomes based on F (OAB) value = 11.128 with p-value = 0.002 < 0.05. (3) Learning outcomes of short-distance running with visual learning media that have higher learning motivation than children learning with audio learning media who have high learning motivation based on Qcount = 15.01 > Qtabel (0.05;4:30) = 3.85. (4) Learning outcomes of short-distance running with visual media and audio media on low learning motivation there was no noticeable or significant difference based on the value of Qcount = 2.39 < Qtabel (0.05;4:30) = 3.85.